Knowledge and home treatment of measles infection by caregivers of children under five in a low-income urban community, Nigeria (2019)
Background: Despite the availability of a safe and effective vaccine for over 50 years, measles remains a leading cause of death among young children in developing countries. Aim: This study assessed the knowledge and home treatment of measles by caregivers of children under 5 years. Setting: Abebi community, Ibadan, Oyo State, Nigeria. Methods: A descriptive cross-sectional study of 509 caregivers of children aged 6 months to 5 years in a semi-urban community in Ibadan was conducted using a multi-stage sampling method. An interviewer administered structured questionnaire was used to collect information on socio-demographic characteristics, knowledge of aetiology, main symptoms and signs, and home treatment of measles. Chi-square test and logistic regression were used to explore associations at 5% level of significance. Results: Most of the caregivers were females (96.3%), married (86.1%) and were the biological parents of the children (90.9%). More than half had good knowledge of the cause (59.7%) and main symptoms and signs (52.8%) of measles. However, the composite knowledge was good in 57.6% of caregivers. Over half (54.4%) of the caregivers reported that their children ever had measles. Majority (91.3%) of caregivers whose children had measles gave home treatment, while 24 (8.7%) sought treatment from health facilities alone. There was a significant association between caregivers’ educational status, age, tribe and marital status and their knowledge of measles; however, tribe was the only significant predictor of knowledge after regression analysis. Caregivers from other tribes were 3.3 times more likely to have good knowledge of measles than Yoruba caregivers. Caregivers who were 35 years and older compared to those younger than 35 years (OR: 0.625; 95% CI: 0.425–0.921) and those who were not currently married compared to those married (OR: 0.455; 95% CI: 0.273–0.758) had lower odds of having good knowledge of measles, respectively. Conclusion: Home treatment by caregivers of children with measles is high. Health education on the cause, prevention and treatment of measles should be provided for caregivers.